2008
DOI: 10.1088/0963-0252/17/2/024012
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation from the pulsed corona discharge in water

Abstract: Quantitative analysis of ultraviolet radiation from the pulsed corona discharge in water with needle-plate electrode geometry (∼1-3 J pulse −1 ) was performed using the potassium ferrioxalate actinometry. Photon flux J 190-280 and radiant energy Q 190-280 of the UV light emitted from the discharge at spectral region 190-280 nm was determined in dependence on the applied voltage (17-29 kV, positive polarity) and the solution conductivity (100-500 µS cm −1 ). The intensity of the UV radiation strongly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(114 citation statements)
references
References 42 publications
9
105
0
Order By: Relevance
“…If the UV intensity is an indirect measure of the temperature inside plasma then we must assume that the temperature inside the negative polarity plasma streamers is much lower than that of the positive polarity since negative streamers emit significantly smaller amounts of UV light [6,7]. As a consequence, the chemistry inside plasma channels is also different for the negative and positive electrode polarity, which is seen from the emission spectroscopy measurements.…”
Section: Emission Spectroscopy Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…If the UV intensity is an indirect measure of the temperature inside plasma then we must assume that the temperature inside the negative polarity plasma streamers is much lower than that of the positive polarity since negative streamers emit significantly smaller amounts of UV light [6,7]. As a consequence, the chemistry inside plasma channels is also different for the negative and positive electrode polarity, which is seen from the emission spectroscopy measurements.…”
Section: Emission Spectroscopy Measurementsmentioning
confidence: 99%
“…This study uses the measurement of hydrogen peroxide that is produced by the positive and negative polarity electrical discharge as an indirect way to get an insight into the processes that take place at the plasma gas-liquid interface. Currently, there are only a few published studies that report hydrogen peroxide production in the positive electrical and negative discharge in water and above the water's surface [5][6][7]. Lukes [6], for example, measured hydrogen peroxide formation at conductivities up to 500 lS/cm and concluded that the UV induced decomposition of hydrogen peroxide is the process that dominates over all other effects, such as electrolyte concentration at such high conductivities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms of bactericidal effect can be greatly different versus the properties of a treated medium and the supply parameters of an electric discharge setup. Main agents causing inactivation of microorganisms at the electric discharge in gas or water are an electric current [12,13], chemical reactive species including bactericides appearing as a result of the electric current passing through a medium containing oxygen and/or nitrogen [14] and ultraviolet radiation accompanying excitation and ionization acts [15].…”
Section: Introductionmentioning
confidence: 99%